9‐Membered Carbocycles: Strategies and Tactics for their Synthesis. Issue 47 (13th March 2018) - Huber, Tatjana; Wildermuth, Raphael E.; Magauer, Thomas
Abstract: Many natural products comprising a nine‐membered carbocyclic core structure exhibit interesting biological effects. However, only a minority have succumbed to their synthesis in the past. The synthesis of functionalized nine‐membered carbocycles still remains a challenging goal for synthetic chemists, mainly due to their high ring strain. Different strategies to overcome the unfavorable enthalpic and entropic factors associated with their formation are highlighted in this Concept article. The presented methods are classified into two different categories: (1) the ring‐expansion of smaller rings or the ring‐contraction of larger rings and (2) the direct cyclization of acyclic precursors. Abstract : Cyclize or expand it ! In this Concept article, different strategies and tactics for the challenging synthesis of functionalized nine‐membered carbocycles are compared and classified into the following categories: the ring‐expansion of smaller rings, the ring‐contraction of larger rings, the direct cyclization of acyclic precursors and the cycloaddition/‐reversion.